Developing a mobile navigation aid - Azrix, Mohamad; Walid, Noor; Zeki, Akram M.; Yalli, Jameel Jameel (IGI Global, 2016)
Previous studies have shown that mobile device is capable of providing navigation aid for both pedestrian and in-car. Crucial to this, is navigation application supported by the mobile platform. This paper proposes a mobile application intended for navigation aid. The application is design using a generic software development process. The application will enable user to navigate within certain vicinity. This will help users to easily find an unfamiliar place. Other function are integrated in the application, such as tasks function for setting the schedule visit, prayer function for du'a and additional information about certain places. The system is developed using the MIT apps inventor software as the main platform, plus the adobe Photoshop for the maps and route purposes. The system works on android platform only. The system is implemented for use in the Kulliyyah of Information and Communication Technology (KICT), International Islamic University Malaysia.